Comparison of Transperineal Ultrasound Cervical Length and Fetal Head- Perineum Distance Measurements with a Simplified Bishop Score in Predicting Induction of Labor Outcome: What is new? - Usman, Mohammed; Oguntayo, Adekunle; Bawa, Umma; Iliyasu, Abbas; Igashi, Joseph (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: The goal of Induction of labor (IOL) is to achieve vaginal delivery and reduce cesarean section. The Bishop score (BS) is the gold standard method to assess cervical status, but it is not flawless, leading to unnecessary interventions. Transperineal ultrasound measurements have been compared with the BS in predicting successful IOL. Yet the results are inconsistent.Aim: This study aimed to compare transperineal ultrasound measurements and a simplified BS in predicting IOL outcomes at Ahmadu Bello University Teaching Hospital (ABUTH) Zaria.Settings and Design: This was a cross-sectional comparative observational study conducted at the labor wards of ABUTH.Materials and Methods: It was conducted among women for IOL at 37–42 weeks between June 2019 and February 2020. Ninety-Seven women were recruited. Each woman, had a transperineal ultrasound cervical length (TPUS-CL) and fetal head perineum distance (FHPD) measured. This was followed by a simplified BS assessment.Statistical Analysis Used: Relevant Data obtained was entered and analyzed using SPSS version 23. The significance level was considered atP< 0.05.Results: The diagnostic accuracy of TPUS-CL (area under the curve (AUC) =0.604,P= 0.084) was better than the simplified BS (AUC = 0.551,P= 0.402). FHPD (P= 0.067, CI = 0.983–1.661) was superior to fetal station (P= 0.832, CI = 0.599–1.890) in predicting the outcome of IOL. The favorable cut-off values for TPUS-CL, FHPD, and BS in our study were ≤ 3 cm, ≤5 cm, and 5 respectively. It demonstrated that TPUS-CL (P= 0.005, AUC = O.750) and FHPD (P= 0.017, AUC = 0.711) are better than simplified BS in predicting success among Primigravidas.Conclusion: TPUS-CL and FHPD measurements are better than the simplified BS in predicting IOL outcome in primigravidae.
Keywords: Fetal head perineum distance; induction of labor; simplified bishop score; transperineal ultrasound cervical length